Synthesis and characterization of manganese (IV) oxide nanowire via hydrothermal method / Subashini Supramaniam - Subashini, Supramaniam (2013)
In this study, single crystalline nanowires of manganese (IV) oxide have been successfully synthesized via soft chemical process through a facile hydrothermal method. Characterization analysis has been carried out for manganese (IV) oxide as-received, as-synthesized, as well as calcinated at 400, 500 and 600ºC. Various characterization techniques have been used such as structural analysis using X-Ray Diffractometer (XRD), surface analysis using Field Emission Scanning Electron Microscope (FE-SEM), chemical composition analysis using Energy Dispersive X-Ray Spectroscopy (EDX), morphology and physical size analysis using Transmission Electron Microscope (TEM), and thermal analysis using Thermogravimetry (TGA). Through these studies, X-ray diffraction revealed that phase transitions occurred for manganese oxide nanowires at calcination temperature 500ºC. The crystallite sizes of manganese oxide nanowires reduces as the calcination temperature increases. FE-SEM analysis shows larger production of manganese oxide nanowires obtained through hydrothermal method and forming into clusters as the calcination temperature increases. EDX test confirmed the presence of manganese and oxygen as dominant elements in the compound. The chemical compositions remain unchanged even after applying higher temperature. An increase in temperature affected the particle size is shown in TEM images. The particle size is reduced as the calcination temperature is increased. This indicates the diameter of the nanowires gets smaller as the heating temperature gets higher forming thinner and longer nanowires. TGA results identified the changes in weight as well as determine the thermal stability as the calcination temperature increases. The decomposition temperature for MnO2 nanowires to reach thermal stability is starting at 600ºC.